2016
DOI: 10.1080/15592324.2016.1261233
|View full text |Cite
|
Sign up to set email alerts
|

Ancient microRNA families that regulate transcription factors are preferentially preserved during plant radiation

Abstract: Essential genes are usually less likely to be lost during evolution, whereas dispensable genes are lost more frequently. Integrating sacred lotus and other plant microRNA (miRNA) data, we found different ancient miRNA families that arose before eudicot radiation exhibit different evolutionary trajectories. Those ancient miRNA families with higher copy and target numbers, and older age are more likely to be retained in plant descendants and more conserved in (hairpin-structured) miRNA gene sequences. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In plants, a large proportion of miRNAs and their mRNA target genes have less than four mismatches [14]; thus, plant miRNAs perform their functions mainly through binding to the AGO1 protein to form RISC, cleaving from the middle of the pairing region to the 5 ‘end of mRNA [15, 16]. Numerous previous studies have confirmed that most of the target genes of plant miRNAs are transcription factors, stress response factors, and F-box proteins [1719], underscoring the central position of miRNAs in the expression and regulation of genes involved in plant development. In addition, studies in recent years have found that plant miRNAs are also involved in signal transduction pathways, plant hormone induction, synthesis and metabolism of organic compounds, and ion transport, indicating the important biological significance of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, a large proportion of miRNAs and their mRNA target genes have less than four mismatches [14]; thus, plant miRNAs perform their functions mainly through binding to the AGO1 protein to form RISC, cleaving from the middle of the pairing region to the 5 ‘end of mRNA [15, 16]. Numerous previous studies have confirmed that most of the target genes of plant miRNAs are transcription factors, stress response factors, and F-box proteins [1719], underscoring the central position of miRNAs in the expression and regulation of genes involved in plant development. In addition, studies in recent years have found that plant miRNAs are also involved in signal transduction pathways, plant hormone induction, synthesis and metabolism of organic compounds, and ion transport, indicating the important biological significance of miRNAs.…”
Section: Introductionmentioning
confidence: 99%